Vietnam : Bayesian Estimation of Output Gap - Maliszewski, Wojciech (IMF Working Papers; Working Paper ;, 2010)
The paper constructs a new output gap measure for Vietnam by applying Bayesian methods to a two-equation AS-AD model, while treating the output gap as an unobservable series to be estimated together with other parameters. Model coefficients are easily interpretable, and the output gap series is consistent with a broader analysis of economic developments. Output gaps obtained from the HP detrending are subject to larger revisions than series obtained from a suitably adjusted model, and may be misleading compared to the model-based measure.